Implementation Of Increasing Brand Awareness "28 Clean Shoes" Through Instagram Social Media Marketing - Noverian Angga Pratama; Erlita Ridanasti (International Journal of Economics, Business and Innovation Research, 2024)
28 Shoes Clean is a business that operates in the shoe washing service sector. The business idea for 28 Shoes Clean emerged because they saw the high trend of wearing sneakers. Apart from that, the number of users and ownership of sneakers has also increased. On the other hand, this phenomenon is not matched by consumers' ability to care for their shoes, so consumers often find their shoes wear out quickly. 28 Shoes Clean offers value propositions that make it superior to other shoe cleaning businesses, such as cheaper prices and providing a guarantee if shoes are not optimally clean. In the context of social media marketing on Instagram, 28 Shoes Clean faces problems in increasing sales and brand awareness which is characterized by minimal visits to the Instagram platform and a less wide audience reach. To deal with this problem, 28 Shoes Clean implemented strategies including content diversification, improving content quality, posting consistency, and more effective promotional strategies. In its implementation, 28 Shoes Clean succeeded in increasing the number of followers or visitors and expanding audience reach by 39.02% during the implementation period.